Comparative Analyses of Physiochemical Parameters of Bottled and Tap Water in Lahore City - Junaid Ali, Nashida Ahmed, Muhammad Younis, Tahmina Soomro, Zaka Un Nisa, Anwar Ali Malik, Naeem Asim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Drinking water quality is of great concern because of different water borne diseases and negative impacts on the health of humans. Increased trend of bottled water usage is seen around the world. The purpose of this study was to analyze the physiochemical and bacteriological quality of tap and bottled drinking water and campare their parameters. Methods: This study is carried out to determine the physicochemical and microbial properties of the bottled and tap water available in the Lahore city of Pakistan.15 different samples of each bottled and tap water were collected from different areas of Lahore. The investigated parameters were mainly total dissolved solid(TDS), dissolved oxygen (DO), total coliform, Pseudomonas, sodium, arsenic, iron, colour and taste using standard analytical techniques available in the laboratory. The data was analyzed by SPSS software. Results: The results showed that among 15 different bottled water samples, 66.7% samples contain pseudomonas bacteria and 26.7% samples were contaminated with total coliform the other parameters (sodium, arsenic, TDS, iron ) were under safe limit whereas 100% of tap water samples were contaminated. Although some parameters of bottled water in Lahore city were within acceptable range, but most of the bottled water was contaminated with total coliform and pseudomonasthatis not safe to the consumers’ health and none of tap water sample was safe. Practical Implication: This study will be made available to readers for the awareness of water quality and its problem concerned. As ill impacts of contaminated water particularly with above mentioned contaminents, include waterborne diseases and other many diseases. Conclusion: It is concluded from this study that the use of bottled drinking water is based on the assumption that it is pure. In thisstudy, 66.7% of bottled water and 100% of tap water samples were contaminated with total coliform and pseudomonas exceeding WHO standards. The findings of our study also suggest that as compared to tap water, the bottled drinking water may be safer to drink. Keywords: water, quality, contamination, bottled water, tap water